The Effect of Social Media Influencers on Purchase Intention: The Role Brand Awareness as a Mediator - Patmawati, Desi; Miswanto, Miswanto (International Journal of Entrepreneurship and Business Management, 2022)
This research focuses on the influence of social media influencers on purchase intention which is mediated by brand awareness. The use of an influencer has indeed been proven to be effective in creating consumer awareness and influencing their purchase intention towards a brand. The impact caused by using influencers to advertise on social media is to attract attention and create awareness among their fans, so that it is expected to increase purchase intention for the advertised product. To prove this, the researchers used a research sample with respondents who are active social media users who often see influencers advertising a product on social media. The number of participants in this study were 210 people. This study used several software for data processing and data testing, namely IBM SPSS Statistics version 15 to test validity and reliability, IBM AMOS version 22 for hypothesis testing, and Sobel test for mediation tests. Data collection started in August 2021 and continued with data processing. Based on the results obtained, of the four proposed hypotheses, all hypotheses are accepted. Social media influencers have proven to have a positive and significant effect on purchase intention, and the effect will be even stronger when mediated by brand awareness. This proves, the presence of an influencer who advertises a brand on social media has proven effective in attracting attention to creating awareness among social media users, especially among their followers. Further results, consumer awareness of a brand after being advertised by this influencer has proven effective in increasing the level of consumer purchase intention because the results have proven significant. That is, when a consumer is aware, he will most likely seek further information so as to enable him to have a purchase intention, either at that time or in the future.